Ways of a avoiding missed dental appointments in UPCD - Antaran, Charmaine G.
Missed appointments have always been a perennial problem of clinicians in UPCD. This study aimed to determine the most effective way of minimizing missed dental appointments. A daily five-week survey among the thirty-seven senior clinicians was conducted from September 2 to October 4, 1996. The respondents were asked the names of their patients, when and how they were given appointments, whether the appointment was filled or missed and the reasons for missed appointments. The method of appointment control, time of appointment, day of appointment, and section where the patient was given appointment were the variables tested. Results showed that there is no statistically significant difference in the outcome of dental appointments between the different methods, time, and day of appointment. Among the four variables, a significant difference was found in the section of appointment. Therefore, in the University of the Philippines. College of Dentistry patient compliance to appointment does not depend on the method, time, and day of appointment. Only the nature of dental service has an effect in recalling patients.